The Road to Data Security in The Digital World: The Past Data Theft Cases - Kim, Kay K. (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2016)
Credit card data theft has been a critical issue in the United States for more than a decade. Many well-known and successful companies, including TJX and Sony, have been the victim of credit card data theft. Most recently, Target and Neiman Marcus, two extremely successful US retailers, have had thousands of customers’ credit card information compromised. This paper details four of the most highly publicized cases of credit card data theft to affect the United States. Additionally, this paper outlines ethical and legal implications to prevent this data theft from continuing to occur in the future.